Documenting and Reporting Implementation Strategies of Vaccination Efforts (DRIVE) framework for fostering systems learning to enhance cross-context replication in immunization programmes - Abdu A. Adamu; Amos Petu; Balcha G. Masresha; Blaise Bathondoli; Rabiu Ibrahim Jalo; Duduzile Ndwandwe; Charles S. Wiysonge (Discover Public Health)
Abstract There is an urgent need to transform immunization programmes into agile learning systems where implementation strategies that are effective within a particular setting can be systematically and rapidly incorporated into policies and practice in other places to drive performance improvement. However, to facilitate the spread of implementation strategies, their documentation needs to be thorough and clear, with adequate granular information about the active components to foster successful cross-context replication. This article unpacks the strategic value of enhancing documentation of implementation strategies and leverages an implementation science lens to propose a framework called Documenting and Reporting Implementation strategies of Vaccination Efforts (DRIVE) that immunization stakeholders including researchers can use. The DRIVE framework has eight sections which include: name of implementation strategy, description of implementation problem, description of implementation context, definition of implementation strategy, mechanism of action of the implementation strategy, specification of the implementation strategy, facilitators, and barriers of successful implementation of the strategy, and additional information. For countries to make faster progress towards the Immunization Agenda 2030, it is essential that systems learning is prioritised in immunization programmes so that useful implementation strategies, both programme-based and research-based, are adequately documented, rapidly spread and sustainably integrated into practice settings across contexts to improve vaccination coverage and other performance indicators.